2023
DOI: 10.3390/v15091890
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex One-Step RT-qPCR Assays for Simultaneous Detection of SARS-CoV-2 and Other Enteric Viruses of Dogs and Cats

Côme J. Thieulent,
Mariano Carossino,
Laura Peak
et al.

Abstract: The severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) was transmitted from humans to dogs and cats (reverse zoonosis) during the COVID-19 pandemic. SARS-CoV-2 has been detected in fecal samples of infected dogs and cats, indicating potential fecal–oral transmission, environmental contamination, and zoonotic transmission (i.e., spillback). Additionally, gastrointestinal viral infections are prevalent in dogs and cats. In this study, we developed and validated a panel of multiplex one-step reverse tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 68 publications
2
14
0
Order By: Relevance
“…In view of our data, we have demonstrated that using our assays in a multiplex format did not affect the analytical parameters. Additionally, these parameters were similar to those from other assays recently developed in our laboratory for the detection of canine enteric viruses and feline respiratory pathogens [69,70]. In this study, two to three log 10 improvement of the LOD 95 was determined when compared to the previously published multiplex PCR assays for the detection of CAdV-2, CDV, CIV, and CPiV [38].…”
Section: Discussionsupporting
confidence: 67%
“…In view of our data, we have demonstrated that using our assays in a multiplex format did not affect the analytical parameters. Additionally, these parameters were similar to those from other assays recently developed in our laboratory for the detection of canine enteric viruses and feline respiratory pathogens [69,70]. In this study, two to three log 10 improvement of the LOD 95 was determined when compared to the previously published multiplex PCR assays for the detection of CAdV-2, CDV, CIV, and CPiV [38].…”
Section: Discussionsupporting
confidence: 67%
“…These positive samples for CCoV, CRV, CPV and CDV had Ct values of 7.68- 35.83, 15.34-35.22, 8.46-35.06, and 9.25-35.11, respectively. The positivity rates of CCoV, CRV, CPV, and CDV in the 1028 clinical samples with the reference assay [24] were 9.05% (93/1028), 0.88% (9/1028), 25.68% (264/1028), and 4.86% (50/1028), respectively.…”
Section: Detection Results Of Clinical Samplesmentioning
confidence: 97%
“…The 1028 clinical samples collected from December 2021 to June 2023 were tested by multiplex RT-qPCR, as reported by Thieulent et al [24], for CCoV, CPV, CRV, and/or CDV. The assay described by Thieulent et al [24] used quadruplex RT-qPCR to detect the CCoV ORF5 gene, CPV VP2 gene, CDV Phosphoprotein gene, and canine adenovirus-1 (CAdV-1) Hexon gene, and it used duplex RT-qPCR to detect the CRV NSP3 gene and SARS-CoV-2 N gene.…”
Section: Detection Of Clinical Samplesmentioning
confidence: 99%
See 2 more Smart Citations